Advancements in the mechanistic understanding of the copper-catalyzed azide–alkyne cycloaddition - Berg, Regina; Straub, Bernd F (Beilstein journal of organic chemistry, 2013)
The copper-catalyzed azide–alkyne cycloaddition (CuAAC) is one of the most broadly applicable and easy-to-handle reactions in the arsenal of organic chemistry. However, the mechanistic understanding of this reaction has lagged behind the plethora of its applications for a long time. As reagent mixtures of copper salts and additives are commonly used in CuAAC reactions, the structure of the catalytically active species itself has remained subject to speculation, which can be attributed to the multifaceted aggregation chemistry of copper(I) alkyne and acetylide complexes. Following an introductory section on common catalyst systems in CuAAC reactions, this review will highlight experimental and computational studies from early proposals to very recent and more sophisticated investigations, which deliver more detailed insights into the CuAAC’s catalytic cycle and the species involved. As diverging mechanistic views are presented in articles, books and online resources, we intend to present the research efforts in this field during the past decade and finally give an up-to-date picture of the currently accepted dinuclear mechanism of CuAAC. Additionally, we hope to inspire research efforts on the development of molecularly defined copper(I) catalysts with defined structural characteristics, whose main advantage in contrast to the regularly used precatalyst reagent mixtures is twofold: on the one hand, the characteristics of molecularly defined, well soluble catalysts can be tuned according to the particular requirements of the experiment; on the other hand, the understanding of the CuAAC reaction mechanism can be further advanced by kinetic studies and the isolation and characterization of key intermediates.